Anterior scleritis following intravitreal injections in a patient with rheumatoid arthritis: A case report. Issue 47 (November 2017) - Ryu, So Jung; Kang, Min Ho; Seong, Mincheol; Cho, Heeyoon; Shin, Yong Un
Abstract: Rationale: Surgically induced scleritis is a rare complication following ophthalmologic surgery such as cataract surgery, pterygium excision, strabismus surgery, and retinal detachment repair. Rheumatoid arthritis (RA) is the connective tissue disease most commonly associated with scleritis. Patient concerns: A 70-year-old woman visited our clinic with complaint of visual disturbance, ocular pain, and conjunctival injection in her right eye of 1 month's duration. She had a stable state of rheumatoid factor positive RA and had a history of multiple intravitreal injections placed in the symptomatic right eye due to age-related macular degeneration. Diagnoses: Anterior scleritis induced by multiple intravitreal injections. Interventions: Topical and systemic steroids were administered. Outcomes: Her symptoms and signs were relieved and no significant recurrence has been occurred with the maintenance of low dose oral steroid. Lessons: Surgically induced scleritis can also be induced by not only major surgical trauma but also by relatively minor trauma such as intravitreal injection (especially in patients who have connective tissue disease such as RA).